Disparity in dental out-of-pocket payments among older adult populations: a comparative analysis across selected European countries and the USA - Manski, Richard; Listl, Stefan (International dental journal, 2017)
Background The current study addresses the extent to which diversity exists in dental out-of-pocket (OOP) payments across population subgroups within and between the USA and selected European countries. This represents the final paper in a series in which the previous two papers addressed diversity in dental coverage and dental utilisation, respectively, using similar data and methods. Method We used data from the 2006/2007 Health and Retirement Study (HRS) and from the 2004-2006 Survey of Health, Ageing and Retirement in Europe (SHARE) for respondents ≥51 years of age. We estimated the impacts of dental-care coverage and of demographic, socio-economic and health status on the likelihood and amount of dental OOP payments. Results In the USA, older persons with the least education, lowest income and worst health are most likely to pay nothing OOP for their dental care and, for persons with an OOP payment, the amount of this payment increases with income and education and is higher for persons who are uninsured and in fair or poor health. However, these results were not consistently found in the 10 European countries we studied. Conclusions European countries classified according to social welfare state or the presence of social health insurance (SHI) showed no effect on the likelihood of making payments OOP for dental care nor, when OOP payments were made, on the amounts paid. Variation in generosity of coverage and procedures reimbursed by insurance, even within countries with SHI, as well as differing needs, tastes and access to care across countries, contribute to this finding.